2011
DOI: 10.1080/19312458.2011.596991
|View full text |Cite
|
Sign up to set email alerts
|

Testing Hierarchical Models of Argumentativeness and Verbal Aggressiveness

Abstract: Support was found for a hierarchical model of argumentativeness theory (N = 1541) in which the second-order factors of motivation to argue and verbal aggressiveness exert top-down influence on subsidiary motives and attitudes. Emotional involvement with arguing and emotional involvement with verbal aggressing were added to clarify the originating theory and to improve model fit. The argumentativeness scale was heterogeneous, consisting of distinct ability and motivation to argue factors. Ability to argue had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 39 publications
4
36
0
7
Order By: Relevance
“…Other analyses have shown that the appearance of Machiavellianism is related with the instructors' behavior (Martin, Myers, & Mottet, 2006), since the verbal aggressiveness seems to indicate trai-Psychology A. Bekiari nees' Machiavellian (Bekiari, 2016), as Machiavellians use dishonest and offensive means (Christie & Geis, 1970) and tend to practice divergent behaviors (Zagenczyk et al, 2014), cheating and dominating (Talwar & Lee, 2011), as Machiavellianism can be seen as a reaction to aggressive behavior by educators (McDonald, Donnellan, & Navarrete, 2012). Finally, results are in accordance with other studies supporting that verbal aggressiveness is negatively related with students' intrinsic motivation and instructors' responsiveness (Bekiari, 2012(Bekiari, , 2014Bekiari, Perkos, & Gerodimos, 2015;Hamilton & Hample, 2011) and positively related with assertiveness (Bekiari & Pylarinou, 2017). Additionally, it is revealed that instructors' personality plays a determinant role in students' behavior, emotions, tactics and attitudes (Horn, 2002;Infante & Rancer, 1996;Rancer & Avtgis, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Other analyses have shown that the appearance of Machiavellianism is related with the instructors' behavior (Martin, Myers, & Mottet, 2006), since the verbal aggressiveness seems to indicate trai-Psychology A. Bekiari nees' Machiavellian (Bekiari, 2016), as Machiavellians use dishonest and offensive means (Christie & Geis, 1970) and tend to practice divergent behaviors (Zagenczyk et al, 2014), cheating and dominating (Talwar & Lee, 2011), as Machiavellianism can be seen as a reaction to aggressive behavior by educators (McDonald, Donnellan, & Navarrete, 2012). Finally, results are in accordance with other studies supporting that verbal aggressiveness is negatively related with students' intrinsic motivation and instructors' responsiveness (Bekiari, 2012(Bekiari, , 2014Bekiari, Perkos, & Gerodimos, 2015;Hamilton & Hample, 2011) and positively related with assertiveness (Bekiari & Pylarinou, 2017). Additionally, it is revealed that instructors' personality plays a determinant role in students' behavior, emotions, tactics and attitudes (Horn, 2002;Infante & Rancer, 1996;Rancer & Avtgis, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Communication among instructors and students affects substantially the learning process, behavior, thinking and motivation (Bekiari, 2014;Richmond, McCroskey, Kearney, & Plax 1987). However, verbal aggressiveness is widespread significantly in educational environment (Bekiari, Koustelios, & Sakellariou, 2000;Yaratan & Uludag, 2012;Kikas, Peets, Tropp, & Hinn, 2009) and comprises a feature of destructive communication that erodes human relations (Infante & Rancer, 1996;Infante & Wigley, 1986;Bekiari, Kokaridas, & Sakellariou, 2005;Bekiari, Digelidis, & Sakellariou, 2006;Bekiari, Patsiaouras, Kokaridas, & Sakellariou, 2006;Johnson, Becker, Wigley, Haigh, & Craig, 2007;Myers, Edwards, Wahl, & Martin, 2007;Bekiari, 2012;2016;Rancer & Avtgis, 2014;Bekiari, Perkos, & Gerodimos, 2015;Bekiari & Manoli, 2016;Bekiari & Pylarinou, 2017;Manoli & Bekiari, 2015), while a collaborative form of communication which promotes amity, is reduced (Hamilton & Hample, 2011). Communication form adopted by instructors may lead to students' anti-social behaviors (Claus, Booth-Butterfield, & Chory, 2012;Hassandra, Bekiari, & Sakellariou, 2007).…”
Section: Verbal Aggressivenessmentioning
confidence: 99%
“…The use of arguments facilitates the learning process and encourages cooperative action [43]. Moreover, teachers' argumentativeness is positively correlated with physical, social and scientific attraction [44].…”
Section: Argumentativenessmentioning
confidence: 99%